Research technology: Instrumentation between science, state and industry - Bernward Joerges; Terry Shinn (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper explores a little studied arena that exists between science and technology, an arena in which a singular and important variety of open-ended, multipurpose instrumentation is developed by practitioners (neither scientist nor engineer, call them researchtechnologists) for use in academia, industry, state metrology and technical services, and considerably beyond. The generic instrumentation designed in this almost subterraneously institutionalized/professionalized, interstitial arena fuels both science and engineering work. This involves intermittent crossings of the boundaries that demarcate and protect the conventional cognitive and artefact cultures familiar to many historians and sociologists. Research-technologists thereby comprise a distinctive (but never distinct) transverse science and technology culture that generates a species of pragmatic universality, which in turn provides multiple and diversified audiences with a common repertory of vocabularies, notational systems, images and perhaps even paradigms. Researchtechnology practitioners deliver a lingua-franca that contributes to cognitive, material and social cohesion. Research-technology is about the complementarity between boundarycrossing and the stability/maintenance of boundaries. – – Der Aufsatz diskutiert eine Forschungsarena zwischen Wissenschaft und Technik, die kaum untersucht ist: eine Arena, in der eine eigenartige und wichtige Form anwendungsoffener und einer Vielfalt von Zwecken dienlicher Instrumentierung entwickelt wird, und zwar von Praktikern, die sich weder als Wissenschaftler noch als Ingenieure bezeichnen lassen. Ihre Instrumente, die auf dem basieren, was wir hier research-technology nennen, finden den Weg in zahllose akademische, industrielle, staatliche Anwendungsfelder. Die Bedeutung von research-technology wird darin gesehen, dass ihr grenzüberschreitender Einfluss auf anderweitig wenig verbundene wissenschaftliche und ausserwissenschaftliche Disziplinen und Einrichtungen eine Form pragmatischer Universalität erzeugt. Diese Form von Instrumentierung trägt mit anderen Worten bei zur kognitiven und materiell- technischen Integration von sich fortlaufend differenzierenden intellektuellen, professionellen und institutionellen Strukturen.
Keywords: 300